Resolving the Passiflora guentheri and P. mapiriensis enigma: identifying a third member of Passiflora sect. Simplicifoliae from the eastern Yungas, Bolivia - Kuethe, J.r.; Balderrama, José A.; Fuentes, Alfredo; Justiniano, Hermes; Lanas, Mattias (Phytotaxa, 2025)
Two hereto elusive and misunderstood species of Passiflora sect. Simplicifoliae (Passifloraceae), Passiflora guentheri and P. mapiriensis, have been studied and evaluated. This study has shown maintainable differences between the species confirming their taxonomic separation, but questions are raised regarding their origin information and their type localities. From the manuscripts, both species were described as being collected from the exact same locality, which seem unlikely given their close taxonomic alliance. An expedition to Bolivia revisited this location, but also surveyed a wider area to better understand their actual distribution and evaluate the botanical differences between either species. This has shown some consistent botanical traits that warrant their speciation, and examples are given in this paper. Following an extensive planimetric study of the species from this taxonomic group, a third species, here proposed as Passiflora chaskajina sp.nov. is added to the Bolivian flora. The ecology, history, conservation and distribution of the Bolivian members of P. sect. Simplicifoliae has been commented on in this paper.